Developing Individual and Team Resilience in Elite Sport: Research to Practice. Issue 1 (21st February 2022) - Sarkar, Mustafa; Page, Abigail E.
Abstract: Drawing on the growing body of resilience research in elite sport, and the evaluation of the applied impact of this research with various national and international athletes and teams, the purpose of this article is to discuss the development of individual and team resilience with practical recommendations provided for athletes, coaches, and sport psychology practitioners operating in elite sport. Four overarching practical recommendations are provided to aid the development of individual resilience: ensure clarity of what resilience is and is not, enhance and refine personal qualities, evoke and maintain a challenge mindset, and create a facilitative environment. Furthermore, five psychosocial processes are outlined and practical recommendations are provided to develop team resilience: Transformational leadership, shared leadership, social identity, team learning, and team enjoyment and positive emotions. We hope that this article will help bridge the gap between research and practice in this area.